Adolescents knowledge about contraceptives in a public school in the interior of Pernambuco (Research, Society and Development, 2021)
Contraceptive methods or contraceptives are all resources used by men and women to prevent pregnancy and sexually transmitted diseases. One of the main contraceptive methods of worldwide diffusion are the oral hormonal contraceptives, known as birth control pills, these have been widely used by the female population. In addition to the contraceptive action, this class of drugs has other therapeutic purposes such as treatment of ovarian cysts, treatment of ovarian and endometrial cancer, among others. Based on this, it was intended then to know the behavior profile of adolescents on the subject and assess the level of knowledge about contraceptive methods. As a research instrument, an electronic questionnaire was applied, addressing issues about contraceptive methods, with public high school students aged between 14 and 19 years. The results of the work had the participation of 127 students, within this group 96 (75.6%) people were female and 31 (24.4%) were male, it was also evidenced that 55 (43.3%) of the adolescents do not have guidance in the family environment about education and sexual orientation, and 48 (37.8%) of the interviewees claim not to know the risks of possible drug interactions, while 46 (36.2%) believe that they cannot trigger diseases. It is concluded that teenagers have some information about contraceptive methods, however, it is superficial, making clear the need to improve the dissemination of knowledge about sexual health.